1995
DOI: 10.1093/oxfordjournals.humrep.a135949
|View full text |Cite
|
Sign up to set email alerts
|

Fertilization and early embryolgoy: Lineage tracing demonstrates that blastomeres of early cleavage-stage human pre-embryos contribute to both trophectoderm and inner cell mass

Abstract: We injected a fluorescent lineage tracer (Texas Red-lysine-dextran) into individual blastomeres of donated human diploid 2- to 8-cell pre-embryos and cultured them to blastocysts. Once pre-embryos reached the expanded blastocyst stage, they were fixed and examined in a scanning confocal microscope to identify the location of fluorescent tracer. In successfully injected pre-embryos that developed to expanded blastocysts, we found that randomly injected blastomeres formed both trophectoderm (TE) and inner cell m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
5

Year Published

1998
1998
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 0 publications
0
20
0
5
Order By: Relevance
“…Statistics: two-tailed Fisher's exact test labeling one out of four blastomeres showed that within the structure of the embryo this blastomere participates in both cell types of the blastocyst, i.e. ICM and TE [43]. Some murine studies showed that, depending on the orientation of the second cleavage planes, the four blastomeres expose different developmental capabilities [32,44] and different epigenetic modifications [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Statistics: two-tailed Fisher's exact test labeling one out of four blastomeres showed that within the structure of the embryo this blastomere participates in both cell types of the blastocyst, i.e. ICM and TE [43]. Some murine studies showed that, depending on the orientation of the second cleavage planes, the four blastomeres expose different developmental capabilities [32,44] and different epigenetic modifications [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…They proposed ideas such as cytokinesis being resumed on later cell divisions [8], that multinucleation could be a precursory step of nuclear membrane breakdown during cell division, as a temporary and reversible phenomenon [25], the presence of pseudonuclei with a possible fusion between them afterwards [8,31] and that, even though the blastomeres are totipotential, there is a preference for the chromosomally abnormal cells to allocate in the trophectoderm [34].…”
Section: Discussionmentioning
confidence: 99%
“…The plate was tilted at 1 degree/second (V r ) to reach a total tilt of 20 degrees. To count cells in the mouse blastocyst, the cells were stained with Hochest 33342, as previously reported (Hardy et al 1989, Mottla et al 1995. The stained blastocysts were observed by confocal microscopy (FV-1000 Olympus, Japan) and a 3D image was constructed.…”
Section: Tilting Mouse Embryo Culturementioning
confidence: 99%